Prohibitive Expressions as Traditional Cultural Dynamics among Muslim - Ahmad Jamin; Heri Mudra; Jamal Mirdad (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
It is undeniable that oral traditions such as prohibitive expressions not only lead to careful attitude, but also presents identities as Muslim societies. While their existence remains controversial in Islamic perspectives, more societies believe in their function and contribution over safety, effectiveness, and discipline in a particular situation. Meanwhile, this study investigated oral traditions regarding prohibitive expressions that protect societies from any hazard during pregnancy, babies and child, and marriage. Intensive interviews were employed to collect data from a number of participants selected through purposive sampling. As for results, it is believed that the prohibitive expressions comprised some contexts such as during pregnancy, for babies and child, and marriage. Each expression was a mixture between traditional culture or local wisdom and Islam as a religion with strict rules. Although the expressions were not identified to emerge in Islamic context as a whole, the societies presumably believed in religious supports that allow them to practice the local wisdom without avoiding Islam